A maintenance strategy based on system reliability considering imperfect corrective maintenance and shocks. (February 2022) - Gan, Shuyuan; Song, Zhifang; Zhang, Lei
Highlights: Establish a two-stage maintenance policy considering shocks and imperfect maintenance. Propose a reliability model with changing dependence between degradation and shocks. Optimize the limits of imperfect maintenance activity for two reliability stages. Abstract: In this study, an innovative maintenance strategy is proposed for systems subject to normal degradation and shock process. The shock process is a non-homogeneous Poisson process, and a changing factor is considered for the dependence between the normal degradation and the occurrence intensity of shocks. The system reliability is divided into three stages, based on which maintenance activities are implemented. In Stage 1 and Stage 2, when a fatal shock occurs, corrective maintenance is performed if the number of completed corrective maintenance activities does not reach the allowed limit; Otherwise, the system is replaced. Replacement is always performed once the system reliability decreases to Stage 3. Corrective maintenance is imperfect, with a perfect or minimal effect at certain probabilities. Two control variables, the allowed numbers of corrective maintenance in Stage 1 and Stage 2, are determined to minimize the expected system cost rate, by using Particle Swarm Optimization algorithm. The proposed model and method are illustrated by an example of one sliding spool. The optimal result is verified by checking the results of feasible variables. Furthermore, the proposed maintenance policy is compared with two contrastive maintenance policies. The comparison results show the necessity and effectiveness of the proposed method.